Когнитивные и прагматические особенности украинского военного юмористического дискурса социальных сетей - Храбан, Тетяна; Храбан, Игор; Khraban, Tetyana; Khraban, Ihor (Lesya Ukrainka Eastern European National University, 2019)
Research on humor and laughter is carried out in many areas of cognitive linguistics and psychology, psycho- and sociolinguistics. Humor is viewed as a positive emotion evoked by the cognitive processes of evaluating comical utterances in various social settings (Martin, 2007). The aim of the paper is explore the cognitive and pragmatic aspects of the Ukrainian military humorous discourse in social media. To this end, linguistic methods of discourse analysis, contextual and intuitive logical interpretative analysis, and a psycholinguistic method of content analysis were applied. The study is based on the selected corpus of Internet memes and amusing comments taken from social media and further divided into thematic groups. The results of the study indicate that constructive humor comprising 47 per cent of the analyzed texts tend to be more popular than other psycholinguistic types. Its pragmatic purpose is to provide a positive impact on the process of group formation due to its capacity to facilitate interpersonal contacts between individuals by evoking positive emotions. Self-sustaining humor embracing 33 per cent of the analyzed texts manifests the speaker’s ability to preserve a humorous viewpoint of any life events. “Black humor” and derogatory humor are less frequent in the Ukrainian Army discourse of social media covering only 20 per cent of all analyzed texts.Дослідження гумору й сміху здійснюють у багатьох галузях когнітивної лінгвістики та психології, психо- та соціолінгвістики. Гумор розглядають як позитивну емоцію, викликану когнітивними процесами оцінки комічних висловлень у різних соціальних ситуаціях (Martin, 2007). Мета дослідження полягає в установленні когнітивнопрагматичних характеристик українського військового гумористичного дискурсу в соціальних мережах. Для досягнення поставленої мети застосовано лінгвістичні методи дискурс-аналізу, контекстуального та інтуїтивно-логічного інтерпретативного аналізу, а також психолінгвістичний метод контент-аналізу. Вивчення ґрунтується на вибарному корпусі інтернет мемів та комічних коментарів, взятих із соціальних мереж і поділених на тематичні групи. Результати дослідження засвідчили, конструктивний гумор, що охоплює 47% всіх проаналізованих текстів, має тенденцію до частотнішого використання, порівняно з іншими психолінгвістичними типами. Його прагматична мета – здійснити позитивний уплив на процес формування групи через його здатність полегшувати міжособистісні стосунки між комунікантами на основі позитивних емоцій. Самопідтримувальний гумор, що зафіксовано в 33% випадків, демонструє вміння мовця зберігати жартівливий погляд на будь-які життєві події. «Чорний» і зневажливий гумор менш поширені у дискурсі українських військових, складаючи разом 20% усіх прикладів.
Cognitive and Pragmatic Features of the Ukrainian Army Humorous Discourse in Social Media
Keywords: гумор; український військовий гумористичний дискурс; соціальні мережі.; humor; Ukrainian Army humorous discourse; social media